Straight talk, no chaser how to find, keep, and understand a man - Harvey, Steve 1956-; Millner, Denene (Amistad, 2010)
Zeros in on what motivates men and provides tips on how women can use that knowledge to get more of what they need out of their relationships, whether it's more help around the house, more money in the joint bank account, or more truth when it comes to the hard questions concerning commitment, fidelity, jealousy, support, and children